ЭЛЕКТРОН ЎҚУВ КУРСЛАРИ (ЭЎК)НИ ЯРАТИШ - Алламбергенова, М.; Зарипов, Қ.О. (SCIENCE and SOCIETY, 2017)
The article deals with the criteria of creating e-learning course and their using in teaching process with the help of modern pedagogical technologies. This e-learning course includes the complex of all e-learning courses in subjects of school course.